Recurrent Pregnancy Loss in Women with Killer Cell Immunoglobulin‐Like Receptor KIR2DS1 is Associated with an Increased HLA‐C2 Allelic Frequency. (21st November 2015) - Dambaeva, Svetlana V.; Lee, Dong Hyung; Sung, Nayoung; Chen, Chi‐Yao; Bao, Shihua; Gilman‐Sachs, Alice; Kwak‐Kim, Joanne; Beaman, Kenneth D.
Abstract : Problem: During human pregnancy, the uterine lining is highly populated with killer‐immunoglobulin‐like receptor (KIR)‐expressing NK cells that recognize HLA‐C molecules on trophoblast cells. The goal of this study was to analyze the KIR gene contents and frequencies in a N. American cohort of women with RPL of unknown etiology to evaluate whether there is a genetic susceptibility to RPL based on a woman's KIR repertoire and her HLA‐C group, as well as the HLA‐C group of the partner. Method of study: The frequencies of KIR and HLA‐C1 and HLA‐C2 genes were evaluated in 139 Caucasian women with RPL; HLA‐C1, and HLA‐C2 group genes were analyzed in their partners ( n  = 42). The gene frequencies were compared with data reported from corresponding populations. Results: Overall, the frequencies of HLA‐C groups and KIR genes and genotypes in RPL cohort resembled the frequencies for US Caucasians. The HLA‐C1 and HLA‐C2 group distribution was significantly different between women with or without KIR2DS1 . Women positive for KIR2DS1 (45.3% of the study cohort) had an increased frequency of its ligand, HLA‐C2 (0.5159 versus 0.3684 in KIR2DS1 negative women, P  =   0.014). Conclusion: Our results indicate that among KIR2DS1 pos women, the co‐expression of HLA‐C2 is associated with RPL.